Genome-wide investigation of AP2/ERF gene family in the desert legume Eremosparton songoricum: Identification, classification, evolution, and expression profiling under drought stress - Zhao, Mingqi; Haxim, Yakupjan; Liang, Yuqing; Qiao, Siqi; Gao, Bei; Zhang, Daoyuan; Li, Xiaoshuang (Frontiers in Plant Science, 2022)
Eremosparton songoricum (Litv.) Vass. is a rare leafless legume shrub endemic to central Asia which grows on bare sand. It shows extreme drought tolerance and is being developed as a model organism for investigating morphological, physiological, and molecular adaptations to harsh desert environments. APETALA2/Ethylene Responsive Factor (AP2/ERF) is a large plant transcription factor family that plays important roles in plant responses to various biotic and abiotic stresses and has been extensively studied in several plants. However, our knowledge on the AP2/ERF family in legume species is limited, and no respective study was conducted so far on the desert shrubby legume E. songoricum. Here, 153 AP2/ERF genes were identified based on the E. songoricum genome data. EsAP2/ERFs covered AP2 (24 genes), DREB (59 genes), ERF (68 genes), and Soloist (2 genes) subfamilies, and lacked canonical RAV subfamily genes based on the widely used classification method. The DREB and ERF subfamilies were further divided into A1–A6 and B1–B6 groups, respectively. Protein motifs and exon-intron structures of EsAP2/ERFs were also examined, which matched the subfamily/group classification. Cis-acting element analysis suggested that EsAP2/ERF genes shared many stress- and hormone-related cis-regulatory elements. Moreover, the gene numbers and the ratio of each subfamily and the intron-exon structures were systematically compared with other model plants ranging from algae to angiosperms, including ten legumes. Our results supported the view that AP2 and ERF evolved early and already existed in algae, whereas RAV and DREB began to appear in moss species. Almost all plant AP2 and Soloist genes contained introns, whereas most DREB and ERF genes did not. The majority of EsAP2/ERFs were induced by drought stress based on RNA-seq data, EsDREBs were highly induced and had the largest number of differentially expressed genes in response to drought. Eight out of twelve representative EsAP2/ERFs were significantly up-regulated as assessed by RT-qPCR. This study provides detailed insights into the classification, gene structure, motifs, chromosome distribution, and gene expression of AP2/ERF genes in E. songoricum and lays a foundation for better understanding of drought stress tolerance mechanisms in legume plants. Moreover, candidate genes for drought-resistant plant breeding are proposed.